MA’ANIL QURAN: HAQ, HAYAT, HUBB, HISAB DAN HIDAYAH - Nurfadhillah Syam; Abd Haris Nasution; Muhammad Chirzin (IAI Al-Mawaddah Warrahmah Kolaka, 2018)
The Qur'an has a wealth of meaning in the wording of his words. It's simple, but solid. It is global, covering the whole life issue, but is briefly conveyed in its words and sentences. The calculated poverty rate is used as a calculation. As the sun and moon rotate according to the calculation (al-An'am: 96). From the (meaning) of the calculation, he shifted to interpretation in terms of recompense, whether the reply was a reward or a doom (Ali Imran: 199). The meaning of calculations or calculations is then interpreted with sufficient or sufficient that this property is owned by Allah (al-Mujadalah: 8). Then, the reckoning also has a variety of meanings as we have described in the previous chapter. The word Hubb developed in various forms as its derivation. Hibbu (حب) as one of them, means a person who rejoices over his love. then Habab (حبب), it has a neatly articulated tooth meaning as an oath of love. So love is like good teeth and neatly arranged. The word Haqq comes from حق - يحق - حقا. In the dictionary al Munawwir, the meaning of haqq is sure, fixed and proper. In the form of حقيقة means true, original or استحق means entitled. According to Raghib al-Isfahani The word حق is the مطابقة or موافقة which means conformity. The derivation of the lafadz of life in the Qur'an consists of isim and fiil such as استحياء, محيي, محياى, يحي, حية, تحية and so on. Of all the lafadz have their respective positions in their meaning. but in general life in the Qur'an contains several meanings. The word 'hidayah' comes from the root word consisting of three letters, namely 'Ha, Dal, and Ya'. Its meaning revolves around two things, namely 'appear before giving guidance' and 'gentle conveyance'. However, in particular, the meaning of 'hidayah' is defined as something that leads to goodness.